Preactivation of lower extremity muscles during various tumbling take-offs - McNeal, J. R.; Sands, W. A.; Shultz, B. B. (2003)
The purpose of this investigation was to characterize the preactivation of the gastrocnemius and vastus lateralis muscles bilaterally during various tumbling skills characterized by differing body orientations. The stretch-shortening cycle action during the take-off portion of the tumbling skills was analyzed and the results compared across muscles and type of take-off (forward vs backward, twisting vs non-twisting). Thirteen female gymnasts performed 3 trials each of round-off back handspring to 1) backward layout, 2) backward layout with longitudinal axis twist, 3) forward layout and 4) forward layout with longitudinal axis twist. A strain gage adhered to the tumbling surface was used to indicate foot contact and departure during the take-off. The onset of activation of each muscle was assessed as an increase of the EMG of 200% above noise prior to contact in the take-off. Results showed that the gastrocnemius muscle activated earlier than the vastus lateralis, but that this difference was only significant for the backward oriented take-offs. Preactivation was not different between contralateral muscles, providing evidence that unilateral measurements may be sufficient for describing activation of the lower extremity during tumbling take-offs. The results of this study demonstrate that the stretch-shortening cycle activity of the take-off is characterized by different activation patterns for these lower extremity muscles depending on the orientation of the body into and out of the take-off. Therefore, training activities, such as plyometrics, that seek to enhance the stretch-shortening cycle action in gymnasts must be specific to the orientation requirements of each specific skill.